PENGARUH LEADERSHIP, COMPENSATION, REWARD DAN PUNISHMENT TERHADAP WORK DISCIPLINE KARYAWAN PT ANTARMITRA SEMBADA PALEMBANG - Afriansyah, fisok; Faitullah, Faitullah; Hendrayani, Iin; Pratiwi, Nurul Mardiyyah; Siringoringo, Gokmanto (P3M STIE Mulia Darma Pratama, 2025)
Work discipline is an important factor in supporting organizational effectiveness and achieving company goals, which is influenced by leadership, compensation, reward, and punishment. Factors that influence work discipline, namely: ability, leadership, compensation, legal sanctions, and supervision, clear goals of the organization, the existence of regulations owned by the organization, disciplinary behavior of superiors, attention and direction to employees, the existence of rewards and punishments. The purpose of this study is to determine the influence of leadership, compensation, reward and punishment simultaneously on work discipline at PT. Antarmitra Sembada Palembang. The sample in this study amounted to 51 employees. This research method uses quantitative methods. The data analysis method used is descriptive and verification methods. The results of the partial t test regarding the influence of leadership (X1), compensation (X2) and punishment (X4) have a significant influence on work discipline (Y), while reward (X3) does not have a significant effect on work discipline (Y) at PT. Antarmitra Sembada Palembang. The results of the simultaneous f test regarding the influence of leadership (X1), compensation (X2), reward (X3) and punishment (X4) on work discipline (Y) at PT. Antarmitra Sembada Palembang. The test results obtained for Ftable were 2.57. So Fcount (7.247) > Ftable (2.57) and the significant value was 0.000 < 0.05, so it can be concluded that the null hypothesis is rejected and the alternative hypothesis is accepted, meaning that the leadership variables (X1), compensation (X2), reward (X3) and punishment (X4), together have a significant effect on work discipline (Y) at PT. Antarmitra Sembada Palembang.